Attitudes of Croatian consumers about mobile messenger chatbots - Dobrinić, Damir, ekonomist (Array, 2021)
This paper aims to investigate Croatian consumers' attitudes about mobile messenger chatbots (MMC) and their propensity to use them. The proposed conceptual model is based on the Technology Acceptance Model (TAM) and Innovation Diffusion Theory (IDT). The research was conducted through an anonymous survey questionnaire available on the social network Facebook. The empirical research results show that perceived usefulness, perceived ease of use, compatibility, and attitude towards mobile advertisements are statistically significantly related to attitude towards mobile messenger chatbots. No negative correlation was found between internet privacy concern and consumer attitudes about mobile messenger chatbots. A positive correlation was found between attitude towards using mobile messenger chatbots and behavioral intention. In addition to the scientific contribution in better predicting chatbots' acceptance as a communication and promotional tool, the research results will also help marketing experts design advertising campaigns via mobile messenger chatbots.